1987
DOI: 10.1111/j.2042-7158.1987.tb06260.x
|View full text |Cite
|
Sign up to set email alerts
|

Particulate contaminants of intravenous medications and infusions

Abstract: Particulate contamination in small volume parenteral medications has been studied and compared with that found in a selection of large volume infusions. Particle counts in 39 commonly used small volume medications and 7 large volume infusions were performed by an automated light blockage method (HIAC) or by optical microscopy. Based on these results and a random survey of drug therapy of intensive care patients, it is concluded that the contribution of intravenous medications to the total particle load receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…Thus a 1 L LVI can have greater than four times the number of particles Ն10 um and 5 times the number of Ն25 um particles per container as compared to a SVI. This discrepancy in the particle limits for SVI and LVI is relevant due to the sheer volume of parenteral solutions administered to critical care patients and the potential impact of high particle loads on these patients (15,18,30,56). As documented by Nath et al (60) and corroborated by the data, albeit limited, presented in Table II, most injectable product particle level counts fall far below those allowed in USP Chapter Ͻ788Ͼ.…”
Section: Relevant Regulations and Standardssupporting
confidence: 68%
See 1 more Smart Citation
“…Thus a 1 L LVI can have greater than four times the number of particles Ն10 um and 5 times the number of Ն25 um particles per container as compared to a SVI. This discrepancy in the particle limits for SVI and LVI is relevant due to the sheer volume of parenteral solutions administered to critical care patients and the potential impact of high particle loads on these patients (15,18,30,56). As documented by Nath et al (60) and corroborated by the data, albeit limited, presented in Table II, most injectable product particle level counts fall far below those allowed in USP Chapter Ͻ788Ͼ.…”
Section: Relevant Regulations and Standardssupporting
confidence: 68%
“…Estimates are that patients in intensive care receive more than a million injected particles Ͼ2 microns in size daily (18,30,31). One method for controlling the particle load administered to critically ill patients has been through the use of final filters.…”
Section: Numbermentioning
confidence: 99%
“…9 10 12 26 Whatever the administered drug characteristics, fast rates of drug administration are associated with pain, phlebitis, and loss of cannula patency. 30 It could be observed that such errors were less frequent in the two hospitals equipped with CIVA and in the three hospitals that could provide industry prepared ready to use products. These types of products are presented in larger volumes to be infused by slow intravenous infusion.…”
Section: Wrong Rate Errorsmentioning
confidence: 98%
“…High levels of particulate matter are found intrinsically in IV fluids and particularly small volume medications such as reconstituted antibiotics (Backhouse et al 1987). In addition, Walpot et al (1989) found particles of glass, rubber and plastic in IV fluid during administration which he demonstrated (in ICU patients at autopsy) were deposited in the capillary bed, particularly in the lungs, causing endothelial damage and granuloma formation.…”
Section: Use Of the Central Linementioning
confidence: 99%